2015
DOI: 10.1155/2015/937096
|View full text |Cite
|
Sign up to set email alerts
|

Status of Intestinal Parasitic Infections among Primary School Children in Rivers State, Nigeria

Abstract: Status of intestinal parasitic infections among primary school children in Rivers State, Nigeria, was investigated between January and December 2011. A total of 3,826 stool samples were collected from school children (1,828 males and 1998 females) in 36 primary schools from 13 local government areas of Rivers State. The samples were analyzed using wet saline/iodine and formol ether concentration methods. Of the 3,826 stool samples examined, 1059 (27.66%) were positive for different intestinal parasites, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 14 publications
7
29
2
2
Order By: Relevance
“…Also personal hygiene may contribute to this high prevalence but generally the relative humidity, temperature and other environmental factors in Aba are very favourable for the transmission of hookworm in the area. However, the 8.0% recorded is lower than 17.8% reported by Babamale et al, (2015) among school-aged children in Okuta community in Kwara State ;25.0% recorded by Abah and Arene (2015) among school children in Rivers State and 25.5% reported in Ethiopia by Ibrahim et al,(1999). Elsewhere, Odebunmi et al, (2007) had attributed the variation in the prevalence of hookworm to some habits such as the use and abuse of drugs accounting for the low shedding of eggs by infected people thereby giving a false impression of low infection rate.…”
Section: Abah Ae; Wokem Gnmentioning
confidence: 60%
See 1 more Smart Citation
“…Also personal hygiene may contribute to this high prevalence but generally the relative humidity, temperature and other environmental factors in Aba are very favourable for the transmission of hookworm in the area. However, the 8.0% recorded is lower than 17.8% reported by Babamale et al, (2015) among school-aged children in Okuta community in Kwara State ;25.0% recorded by Abah and Arene (2015) among school children in Rivers State and 25.5% reported in Ethiopia by Ibrahim et al,(1999). Elsewhere, Odebunmi et al, (2007) had attributed the variation in the prevalence of hookworm to some habits such as the use and abuse of drugs accounting for the low shedding of eggs by infected people thereby giving a false impression of low infection rate.…”
Section: Abah Ae; Wokem Gnmentioning
confidence: 60%
“…Specifically; prevalence of 25.0% was recorded by Abah and Arene (2015) among school children in Rivers State. Babamale et al, (2015) reported prevalence of 17.8% among school-aged children in Okuta community in Kwara State.…”
mentioning
confidence: 94%
“…However, FMOH survey was only school-based. Most STH prevalence surveys in Nigeria were carried out among school children: Sowemino and Asaolu [31] obtained prevalence of 34.4% in Ile-Ife, Osun State; 26.66% was reported in Rivers State [32], 80.9% among Almajiri children in northern Nigeria [33], and 30.3% in Imo state [9]. Differences in prevalence obtained in various parts of the country relative to the present study may be attributable to environmental, ecological and anthropogenic factors that prevailed in each area.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on prevalence of intestinal parasitic infection among patients of psychiatric institutions have been reported by researchers in other climes; Italy, Ghana, Iran and Egypt [2,5,6,7,8]. In Nigeria several studies have been conducted on the prevalence of parasitic infections in different parts of the country [9,10,11,12]. Information on psychiatric patients in Nigeria in relation to parasitic infections associated with them is fragmentary.…”
Section: Introductionmentioning
confidence: 99%